Understanding the superior mechanical properties of hollow-strut metal lattice materials. (15th April 2023) - Zhong, H.Z.; Song, T.; Li, C.W.; Das, R.; Gu, J.F.; Qian, M.
Abstract: Intricate hollow-strut metal lattice materials are an emerging class of novel metallic cellular materials enabled by additive manufacturing. This work shows that hollow-strut Ti-6Al-4V lattice materials are consistently stronger and stiffer (up to 60% better) than their solid-strut counterparts of the same relative density, both experimentally and through finite element analysis (FEA). The underlying reasons are investigated using analytical models derived from the Timoshenko-beam theory, which considers deformation by concurrent stretching, bending and shear, rather than the single-mode deformation mechanism assumed by the Gibson-Ashby model. Hollow-strut lattices exhibit higher resistance to bending than solid-strut lattices at the same strut length and relative density, thereby leading to increased strength and stiffness. Hollow-strut metal lattices offer an unusual option for lightweight designs, with better mechanical properties at the same or lower density than solid-strut metal lattices. Graphical abstract: Image, graphical abstract